Landscape-Oriented Town Planning as a Factor of Sustainable Development of the Cities in the Irkutsk Region - Bolshakov, Andrey (project baikal, 2019)
Improvement in the urban environment depends on how effectively the environmental benefits of landscapes are used in the system of urban planning and development. The natural framework of the region can support the ecological balance within the environment-society system, while the natural framework of the city offers better hygienic qualities to the urban environment. To find solutions for the improvement of urban environment, a town planner needs to comprehend the boundaries of the natural framework and to know how to formulate town planning requirements in regard to the urban fabric. The case study of the Baikal region and the city of Irkutsk is used to explain the approach to improvement of environmental effectiveness of town planning.
Keywords: ecological qualities of the landscape; landscape-oriented principle; natural framework; planning; development morphotypes; gradient blending of density; urban environment; environmental effectiveness of town planning